2022
DOI: 10.1155/2022/8998231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Magnetic Resonance Imaging Scan, Multislice Spiral Computed Tomography Three‐Dimensional Reconstruction Combined with Plain Film X‐Ray in Spinal Injuries

Abstract: Objective. The main objective is to explore the diagnostic value of magnetic resonance imaging (MRI) scan, multislice spiral computed tomography (MSCT) three-dimensional reconstruction combined with plain film X-ray in spiral injuries. Methods. By means of retrospective study, the data of 100 patients with spiral injury treated in our hospital from January 2020 to December 2021 were retrospectively analyzed, and all patients received MRI scan, MSCT three-dimensional reconstruction, and plain film X-ray examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They offer a low radiation exposure option while providing valuable information, making them an indispensable tool for assessing the spine. Moreover, radiography is capable of revealing the spinal alignment and providing a comprehensive view of the bone structure ( 25 ). By using preoperative radiographic imaging, various factors can be identified hat may aid in stratifying patients and may ultimately enhance surgical treatment and the long-term prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…They offer a low radiation exposure option while providing valuable information, making them an indispensable tool for assessing the spine. Moreover, radiography is capable of revealing the spinal alignment and providing a comprehensive view of the bone structure ( 25 ). By using preoperative radiographic imaging, various factors can be identified hat may aid in stratifying patients and may ultimately enhance surgical treatment and the long-term prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some scholars have advocated for the utilization of MRI in the assessment of lumbar VBQ. MRI’s sensitivity to signal changes related to alterations in bone microstructure, such as trabecular bone fat infiltration and subtle vertebral microdamage [ 27 ], has gradually made it a routine examination for vertebral fractures, particularly in the thoracolumbar fractures of the elderly [ 28 ]. The advantage of measuring lumbar vertebral HU and VBQ through CT and MRI lies in their ability to selectively assess trabecular bone, bypassing the cortical bone [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI's sensitivity to signal changes related to alterations in bone microstructure, such as trabecular bone fat infiltration and subtle vertebral microdamage, 27 has gradually made it a routine examination for vertebral fractures, particularly in the thoracolumbar fractures of the elderly. 28 The advantage of measuring lumbar vertebral HU and VBQ through CT and MRI lies in their ability to selectively assess trabecular bone, bypassing the cortical bone. 13,16 HU, VBQ, and the BMD obtained from DEXA scans all serve as indicators reflecting the vertebral quality.…”
Section: The Current Application Of Lumbar Ct Mri and Dexa In Vertebr...mentioning
confidence: 99%
“…A study by Xin and Lei [19] showed that MRI and MSCT had unique advantages in the diagnosis of spinal injuries, and patients with negative X-ray results could be examined by MRI and MSCT to observe their spinal injuries. In this research, 47 patients were eventually selected with negative X-ray examination result as well as the suspected fractures.…”
Section: Discussionmentioning
confidence: 99%